An Investigation into the Philosophical Differences between Pedagogical and Andragogical Approaches to Education - Ignatius Nnaemeka Onwuatuegwu (Journal of Education Review Provision, 2023)
The aim of this research is to investigate the differences between pedagogical and andragogical approaches to education. Pedagogy is commonly used in schools and universities and assumes that learners are passive and require instruction. In contrast, andragogy, which was created by Malcolm Knowles, assumes that learners are self-directed and take an active role in their learning. The study will analyze the beliefs and values underlying these approaches and how they impact the educational experiences of both teachers and students. The ultimate goal is to gain a better understanding of the philosophical basis of these approaches and their potential impact on the future of education.